Analisis Perbandingan Anggaran Pendidikan di Negara Nigeria dan Kongo - Yuliati; Komarudin Sassi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Education is one of the main pillars of social and economic development, especially in developing countries. Generally, education not only serves as a means of knowledge transfer but also plays a crucial role in shaping individual character and skills. In developing countries, education can be a tool to address various challenges such as poverty, social injustice, and economic inequality. In the context of analyzing education budgets in Nigeria and Congo, the most suitable research design is mixed methods research. This approach combines quantitative and qualitative methods, allowing researchers to gain a deeper and more comprehensive understanding of the phenomena under study. A comparison of education budgets in Nigeria and Congo shows significant differences in the allocation and management of educational resources. Nigeria, with a larger budget allocation, has the potential to improve the quality of education, while Congo faces more fundamental difficulties with relatively low budget allocation. The factors influencing education budgets in both countries are highly variable.